Kajian Kritis Pemanfaatan Thermal Barrier Coating Keramik Terhadap Efisiensi Termal Dan Keandalan Mesin Suhu Tinggi - Moh. Syaiful Anwar; Didit Darmawan; M. Andrean Maulana; Dimas Tri Radityo; M. Firnanda Fahrul Ulum (Journal of Innovative and Creativity, 2026)
This study critically reviews the use of Thermal Barrier Coating (TBC) on engine components by examining microstructure stability, long-term heat resistance, and the effect of coating quality and material composition on thermal efficiency and resistance in aggressive working environments. Advances in manufacturing technology have opened up new opportunities for the use of Thermal Barrier Coatings (TBC) to protect engine components operating at extreme temperatures, such as internal combustion engines and gas turbines. This study examines the microstructural stability and long-term heat resistance of Yttria-Stabilized Zirconia (YSZ)-based TBC against repeated thermal cycles and high-temperature oxidation, as well as the influence of coating quality, deposition method, and material composition on thermal efficiency and coating resistance. A qualitative method with literature studies was chosen to synthesize empirical findings from various reliable studies. The results show that TBC maintains a stable columnar structure up to a temperature of 1200°C, but undergoes phase degradation at higher temperatures or repeated thermal cycles, which can reduce mechanical and thermal performance. The growth of Thermally Grown Oxide (TGO) at the bond coat-top coat interface is a critical factor in layer durability, with proper composition and process control capable of maintaining durability. In addition, coating quality and material composition play an important role in heat insulation efficiency and resistance to corrosion and erosion. This study recommends optimizing ceramic materials, microstructure engineering, and deposition techniques to improve the service life and thermal efficiency of modern engine systems. This research provides essential knowledge for the development of reliable and efficient thermal coating technology